2017
DOI: 10.5539/ijel.v7n5p74
|View full text |Cite
|
Sign up to set email alerts
|

“Dragon and Bear”: A SF-MDA Approach to Intersemiotic Relations

Abstract: Compared with analysing the meaning of discourse from the perspective of language only, multimodal discourse analysis embarking on modes like images, words, colour, sound and other elements can help understand the underlying meaning expressed more thoroughly. Systemic functional multimodal discourse analysis (SF-MDA) built upon systemic functional theory (SFT) is employed in this study. An illustrated article issued in The Economist is taken as an example to fully dredge the intersemiotic relations between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Meanwhile, other social semiotic resources such as images, color, music, gestures and embodied action are defined as non-linguistics. Since this study involved verbal and visual rhetoric modes, SF helps to investigate linguistics while Kress & van Leeuwen's visual grammar, generated from SFG, examines non linguistics (Kress & van Leeuwen, 2006), (Jewitt, 2014), and (Gao, 2017). As stated, SF-MDA approach is adapted from Halliday's premise that the organization of semiotic resources manifests the social function that the resources play in social interaction.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…Meanwhile, other social semiotic resources such as images, color, music, gestures and embodied action are defined as non-linguistics. Since this study involved verbal and visual rhetoric modes, SF helps to investigate linguistics while Kress & van Leeuwen's visual grammar, generated from SFG, examines non linguistics (Kress & van Leeuwen, 2006), (Jewitt, 2014), and (Gao, 2017). As stated, SF-MDA approach is adapted from Halliday's premise that the organization of semiotic resources manifests the social function that the resources play in social interaction.…”
Section: Theorymentioning
confidence: 99%
“…Hermawan discussed the creation of messages of Elementary School English textbook for Indonesian using the collaboration of images and language (Hermawan, 2013). In order to carefully examine sociocultural differences and problems between China and Russia, Gao explained the intersemiotic relation between text and images (Gao, 2017).…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…The previous studies related to SF-MDA have been found in many papers. They focused on advertisement (Enli, 2014), language acquisition (Liu, 2022), magazine (Gao, 2017), and tweets (Wignell et al, 2021), to mention a few. In academic discourse, the frameworks have been intensively used to investigate cohesion found in international postgraduate business students' multimodal written texts (Alyousef & Alnasser, 2015), thematic progression in Saudi Postgraduate Business Students' multimodal texts (Alyousef & Alsharif, 2019), theme and information structure (Alyousef, 2020a), the Textual and the Logical Cohesive Devices in a Postgraduate Accounting Course (Alyousef, 2020b), and experiential meaning in Saudi Postgraduate Business Students' multimodal accounting texts (Alyousef & Alsharif, 2017).…”
Section: Introductionmentioning
confidence: 99%